Biomass Production of Root and Shoot of Talinum paniculatum Gaertn. by Liquid and Solid Ms Medium with Plant Growth Hormone IBA - Muhammad Hamzah Solim; Y. S. Wulan Manuhara (Journal of Tropical Biodiversity and Biotechnology, 2016)
Talinum paniculatum Gaertn. is one of traditional medicinal plant in Indonesia which has benefits such as for vitality and maintain blood circulation. The aim of this research is to obtain biomass production of root and shoot of T. paniculatum Gaertn. by liquid and solid MS medium with IBA. This research conducted to provide biomass as raw material for secondary metabolites test. Stems as explant were induced with four treatments (liquid MS, solid MS, liquid MS + 2 ppm IBA and solid MS + 2 ppm IBA) with five repetitions. Observation did for 28 days. The parameters are the percentage of explants which formed the root and shoot, morphology, fresh and dry biomass. Result shows that percentage of root and shoot have 100% in liquid and solid MS + 2 ppm IBA. Fresh and dry biomass of root and shoot in solid MS + 2 ppm IBA higher than the others. This research found callus in liquid and solid MS + 2 ppm IBA. Morphology of root in liquid MS has thin and friable, but thick in solid MS. Shoot in solid and liquid MS has thin, short and sturdy.